The additional costs of antibiotics and re-consultations for antibiotic-resistant Escherichia coli urinary tract infections managed in general practice. - Alam, M; Cohen, D; Butler, C; Dunstan, F; Roberts, Z; Hillier, S; Palmer, S (2009)
The emergence of antibiotic resistance is a major threat to public health. In the UK, most antibiotics are prescribed in general practice but the extra costs to general practice of resistant infections have not previously been well described. We compared the costs of treating patients presenting with resistant Escherichia coli urinary tract infections (UTIs) (resistant to ampicillin, trimethoprim or at least one antibiotic) with the costs of treating patients with UTIs that were sensitive to all six tested antibiotics (ampicillin, trimethoprim, amoxicillin/clavulanic acid, cefalexin, ciprofloxacin and nitrofurantoin) with regard to re-consultations and antibiotics prescribed. There were significantly higher antibiotic costs (mean extra antibiotic cost 1.19 pounds/1.75 euros), re-consultation costs ( 2.42 pounds/3.55 euros) and total costs ( 3.62 pounds/5.31euros) for patients whose infections were resistant to at least one antibiotic compared with those with sensitive infections even after accounting for potentially confounding factors. Although these per-patient costs may appear small, they do not take into account the full additional costs of resistant UTIs in the community and, given the high prevalence of UTIs, the overall costs to the health service are substantial.